Maternal Dietary Docosahexaenoic Acid Alters Lipid Peroxidation Products and (n-3)/(n-6) Fatty Acid Balance in Offspring Mice - Yang, Bo (Metabolites, 2019)
The abundance of docosahexaenoic acid (DHA) in the mammalian brain has generated substantial interest in the search for its roles in regulating brain functions. Our recent study with a gene/stress mouse model provided evidence to support the ability for the maternal supplement of DHA to alleviate autism-associated behavior in the offspring. DHA and arachidonic acid (ARA) are substrates of enzymatic and non-enzymatic reactions, and lipid peroxidation results in the production of 4-hydroxyhexenal (4-HHE) and 4-hydroxynonenal (4-HNE), respectively. In this study, we examine whether a maternal DHA-supplemented diet alters fatty acids (FAs), as well as lipid peroxidation products in the pup brain, heart and plasma by a targeted metabolite approach. Pups in the maternal DHA-supplemented diet group showed an increase in DHA and a concomitant decrease in ARA in all brain regions examined. However, significant increases in 4-HHE, and not 4-HNE, were found mainly in the cerebral cortex and hippocampus. Analysis of heart and plasma showed large increases in DHA and 4-HHE, but a significant decrease in 4-HNE levels only in plasma. Taken together, the DHA-supplemented maternal diet alters the (n-3)/(n-6) FA ratio, and increases 4-HHE levels in pup brain, heart and plasma. These effects may contribute to the beneficial effects of DHA on neurodevelopment, as well as functional changes in other body organs.